Phenolate-induced intramolecular ring-opening cyclization of N-tosylaziridines: access to functionalized benzoxacycles. Issue 32 (2nd August 2018) - Devi, Runjun; Das, Jonali; Sarma, Bipul; Das, Sajal Kumar
Abstract : Phenolate-induced, diastereo- and regioselective intramolecular exo -tet ring-opening cyclization of N -tosylaziridines has been achieved for the first time. Abstract : Phenolate-induced, diastereo- and regioselective intramolecular exo -tet ring-opening cyclization of N -tosylaziridines has been achieved for the first time. The N -tosylaziridine substrates bearing a tethered ( ortho -( tert -butyldimethylsiloxy))aryl substituent, prepared directly from the corresponding olefins under Sharpless aziridination conditions, furnished functionalized 2, 3-dihydrobenzofuran, chroman, and 1-benzoxepane derivatives in excellent yields when treated with tetrabutylammonium fluoride (TBAF) at room temperature. Our ability to synthesize benzoxacycle-based N -tosyl-protected amino alcohols, that are otherwise difficult to obtain by traditional synthetic routes, has opened the door to diversify the chemistry of β-amino alcohols. We also succesfully performed the Baeyer–Villiger oxidation of a salicylaldehyde ether bearing a tethered N -tosylaziridine moiety with m -CPBA followed by tandem saponification and 6- exo -tet aziridine ring-opening cyclization, furnishing the corresponding trans -3, 4-disubstituted-1, 4-benzodioxane derivative. Overall, the study has unveiled a new entry to the synthesis of benzoxacycles and has also broadened the impact of aziridines as synthetic building blocks.